KAJIAN BEBAN PENCEMARAN LIMBAH USAHA KECIL DI SUNGAI CILIWUNG SEGMEN KOTA BOGOR - Agus Priyono (Media Konservasi, 2011)
Ciliwung River had existed and become an important part of the community since ancient period.  However, along with the passing period and the rapid development, it had become polluted with various waste and garbage being disposed off to the river from its upstream to its downstream segments.  Small businesses were among those who polluted the river and degraded the quality of Ciliwung water. This study was aimed at identifying the load of pollution caused by small business waste disposal to Ciliwung River.  The result showed that most of the small businesses in Bogor Municipal Region disposed their waste directly to Ciliwung River and caused high load of pollution to the river.  Among the industry were the tofu (soybean curd), tempe (fermented soybean cake), tapioca flour, and cow husbandry businesses.  The calculation resulted in a total of pollution load from small businesses of 605.5 ton/year which caused the water of Ciliwung River had the BOD of 174.5 mg/l in the dry season and 1.62 mg/l in the rainy season due to its debit in both season.  The load of pollution in Ciliwung River caused by small businesses should be controlled in accordance with its capacity to hold pollution.  The strategy should include lowering pollution load disposed off by the small businesses, arranging the spatial distribution of the businesses, and developing environmental friendly/green technology for the businesses.  Keywords: pollution, small businesses, waste disposal, Ciliwung River, Bogor segment.